Correction to the article “Abnormal Uterine Bleeding in Adolescents: A Multidisciplinary Approach”, Published on Acta Med Port 2021 Apr;34(4):291-297. - Ramalho, Inês (2021)
On page 293, last paragraph on the left side column, where it reads:“We will discuss in detail the approved pharmacologic agents to treat acute AUB in adolescents, followed by a pharmacologicalmanagement algorithm, taking in consideration the hemodynamic stability and the haemoglobin level.8,9,15” It should read:“We will discuss in detail the approved pharmacologic agents to treat acute AUB in adolescents, followed by a pharmacologicalmanagement algorithm, taking in consideration the hemodynamic stability and the haemoglobin level [Appendix 1 (see Appendix 1: https://www.actamedicaportuguesa.com/revista/index.php/amp/article/view/12829/Appendix_01.pdf)].8,9,15”Article published with errors: https://www.actamedicaportuguesa.com/revista/index.php/amp/article/view/12829